Molecular Characterization of a Native Nematode, Pristionchus pacificus (Nematoda Class: Rhabditida: Diplogastridae) From Avocado Soils in Mexico - Flores-Pantoja, Luis Enrique; Sánchez-Saavedra, Ma. Guadalupe; Gutiérrez-Cárdenas, Oscar Giovanni; Zepeda Jazo, Isaac (Revista Colombiana de Entomología, 2025)
Avocado Persea americana Mill., is a crop of great economic importance in Mexico and it is affected by pests that cause significant damage. Traditionally, pest control in avocado crops has been based on the use of organosynthetic pesticides; however, their excessive and indiscriminate use has negative effects on the environment, health, and quality of the fruit. In the search for more sustainable alternatives for the control of agricultural pests, the use of entomopathogenic nematodes (EPNs) as biological control agents is one of the most promising options. To explore possible EPNs associated with avocado crops, soil samples were collected from six avocado orchards in the municipality of Atapan, Michoacán, Mexico, and possible entomopathogenic agents were isolated using the bait insect technique with Galleria mellonella larvae. The molecular characterization through partial sequencing of the SSU (Small Subunit) and ITS (Internal Transcribed Spacer) regions of strain ANP003 confirmed that one of the isolates corresponds to the species Pristionchus pacificus, this represents the first report in Mexico of a nematode associated with avocado crop. The genetic distance analysis of SSU-18S allowed us to know the close relationship of this isolate with the entomopathogenic nematode Pristionchus entomophilus.